2009
DOI: 10.2165/11318060-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Limited Sampling Models and Bayesian Estimation for Mycophenolic Acid Area under the Curve Prediction in Stable Renal Transplant Patients Co-Medicated with Ciclosporin or Sirolimus

Abstract: Use of the developed multiple linear regression equation and Bayesian estimator, both based on only three blood sampling times within 2 hours following a dose of mycophenolate mofetil, allowed an accurate prediction of a patient's MPA AUC(12) for therapeutic drug monitoring and dose individualization. These findings should be validated in a randomized prospective trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 36 publications
6
54
1
Order By: Relevance
“…The initial pharmacokinetic model of Li et al (6), which was developed in 402 HCT recipients, was modified to include total MPAG (as described by Musuamba et al (15)) and unbound MPA concentrations. Briefly, total MPA pharmacokinetics was described using a two-compartmental model with first-order elimination and first-order absorption with a lag time (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The initial pharmacokinetic model of Li et al (6), which was developed in 402 HCT recipients, was modified to include total MPAG (as described by Musuamba et al (15)) and unbound MPA concentrations. Briefly, total MPA pharmacokinetics was described using a two-compartmental model with first-order elimination and first-order absorption with a lag time (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The latest published studies investigating population pharmacokinetics of MPA and including a mechanism-based model for EHC are those by Musuamba et al [91] and de Winter et al [92] Musuamba et al [91] developed a model with a compartment to describe EHC in stable renal transplant recipients who were co-medicated with sirolimus (tables I and II). The application of Bayesian estimation allowed for accurate prediction of MPA AUC from 0 to 12 hours (AUC 12 ) and individualized dosing.…”
Section: Outline Of Population Pharmacokinetic Modelling Of Mpa Pumentioning
confidence: 99%
“…In summary, the review of the published papers found 12 studies [26,42,67,68,70,71,8389,91,92] using NONMEM to describe the pharmacokinetics of MPA in renal transplant patients. Only one study included children [68] and one study used Win-NonLin.…”
Section: Outline Of Population Pharmacokinetic Modelling Of Mpa Pumentioning
confidence: 99%
“…A number of studies have tested Bayesian procedures for estimation of MPA AUC and shown satisfactory predictive power. [50][51][52][53] Disadvantages of Bayesian methods include a more complex calculation requiring specialist software and user training and reliance on the existence of an appropriate pharmacokinetic model and knowledge of covariates. 16 Thus, it is less easily applicable on a routine basis in the clinical setting, although web-based services are available to assist (http//pharmaco.chu-limoges.fr/abis.htm).…”
Section: Discussionmentioning
confidence: 99%